Gender wage gaps in Chile. A long term view: 1958 - 1990 - Paredes, Ricardo; Riveros, Luis (Estudios de Economía, 2016)
Using a statistical technique to correct for the presence of the selectivity bias, this paper estimates gender wage gaps in Chile for the period 1958-1990. Gender wage gaps are decomposed into an “endowment” effect –associated with different stocks of human capital- and a “discrimination” effect –associated with different returns. The paper argues that a tight labor market would increase the cost of discriminatory practices, fostering the reduction in wage gaps. The evidence reposts that observed changes in gender wage gap largely respond to the economic cycle, suggesting that anti-discriminatory policies must be considered only as a complement to policies aimed at attaining sustainable economic growth.